Central Modulation of Neuroinflammation by Neuropeptides and Energy-Sensing Hormones during Obesity - Maldonado Ruiz, Roger Alexis; Fuentes Mera, Lizeth; Camacho, Alberto (2017)
Centralnervoussystem(CNS)sensesenergyhomeostasisbyintegratingbothperipheralandautonomicsignalsandrespondingto thembyneurotransmittersandneuropeptidesrelease.Althoughitispreviouslyconsideredanimmunologicallyprivilegedorgan, we now know that this is not so. Cells belonging to the immune system, such as B and T lymphocytes, can be recruited into the CNS to face damage or infection, in addition to possessing resident immunological cells, called microglia. In this way, positive energybalanceduringobesitypromotesaninflammatorystateintheCNS.Saturatedfattyacidsfromthediethavebeenpointed out as powerful candidates to trigger immune response in peripheral system and in the CNS. However, how central immunity communicatestoperipheralimmuneresponseremainstobeclarified.Recentlytherehasbeenagreatinterestintheneuropeptides, POMC derived peptides, ghrelin, and leptin, due to their capacity to suppress or induce inflammatory responses in the brain, respectively. These may be potential candidates to treat different pathologies associated with autoimmunity and inflammation. In this review, we will discuss the role of lipotoxicity associated with positive energy balance during obesity in proinflammatory responseinmicroglia,BandTlymphocytes,anditsmodulationbyneuropeptides.